Viscosity and Antiwashout Properties of Cement Mortar at Low Temperature Seawater Environment - Chang Kim, Heon; Jang, In-Kyu; Park, Seung-Kyu (Asian Journal of Chemistry, 2014)
Cement mortar is a construction material and generally a mixture of water, cement, sand and sometimes fine gravel. When cement mortar is applied to the seawater construction at low temperature below 0 °C, the flow performance, workability, placement, antiwashout and consolidation should be considered in combination. In this research, the antiwashout and rheological properties of the cement mortar have been investigated with admixtures prepared by adding anionic surfactants, cationic surfactants and polymeric thickeners. Cement mortar formulated by pseudo-polymeric systems, electrostatic association of anionic and cationic surfactants and polymer additive such as poly methyl vinyl ether, showed thixotropic, suitable antiwashout, proper workability and self-leveling properties. Addition of isopropyl alcohol to mixed surfactant admixture decreases the freezing temperature of cement grout to -7 ºC and increases the workability at cold seawater, but slightly decreases the compressive strength of the cement grout at seawater system.